Working Capital Management Practices and its Impact on Profitability, Value and Risk: An Analysis of Sri Lanka Manufacturing Companies. - Koperunthevy, K. (Vavuniya Campus of the University of Jaffna., 2010)
Most of the financial and investment theories focuses on long – term financial discussions to maximize the profit. However, short-term financial matrix of working capital management is to be analyzed to determine the short term assets and liabilities in order to determine the operating liquidity profitability and risk as well. The present study investigates the relative relation between the aggressive/conservative working capital policies and profitability, value and risk of manufacturing companies. The sample consists 50 manufacturing companies listed in the Colombo Stock exchange (CSE) during the period of 2003-2007. Return on Total Assets (ROTA) and Return on Equity (ROE) are used to determine the profitability value of the firms is measured by the market return of Tobin Q. The risk is calculated by using the standard deviation of sales, ROTA, ROE and Tobin Q. Five years data was analyzed by using the Ordinary Least Square (OLS) regression method. The results show that the investment policy positively impact on profitability of ROTA and financing policy negatively affect the ROTA. ROE is positively related with both policies and Tobin Q value is negatively determined by the investment policy and positively affected by the financing policy. It is found that the working capital policy affects the risk of the firm; this is proved by the relation of standard deviation of ROE and working capital policy. Therefore the study concludes that the working capital management policy impact the profitability value and risk of the manufacturing companies.
Keywords: Working capital.; Investment policy; Financing policy; Performance